Anthropogenic soils - Howard, Jeffrey L. (Springer, 2017)
This book is a state-of-the-art review of the physical, chemical and mineralogical properties of anthropogenic soils, their genesis morphology and classification, geocultural setting, and strategies for reclamation, revitalization, use and management.
Keywords: Anthropogenic soils.; Nature -- Effect of human beings on.; Soil and civilization.; elektronické knihy; electronic books